PENGARUH EXPERTISE, REPUTATION, DAN USABILITY TERHADAP REPURCHASE INTENTION MELALUI RELATIONSHIP QUALITY PADA ON-LINE TICKETING AIR ASIA DI SURABAYA - INDRAWATI, VIVI (Universitas Katolik Widya Mandala Surabaya, 2012)
The study was done in order to test the expertise, reputation, and usability of repurchase intention relationship quality through on-line ticketing on Air Asia in Surabaya. The data used were collected through a questionnaire to provide an assessment through a Likert scale from one to five. Data analysis using structural equation modeling (SEM) via LISREL 8.80 program assistance. Object of research or consumer respondents was 150 Air Asia in Surabaya. The results showed that the reputation and usability have an influence on relationship quality, whereas expertise has no significant influence on relationship quality. Other results also provide information that relationship quality affects repurchase intention. Influence of relationship quality on repurchase intention to bring the effort to improve the relationship quality, so there is interest to use the services of Air Asia in the future. This will be beneficial to create loyalty as their capital in a tight competition.